Additional Measurement for Financial Inclusion Indexing and its Impact of Economic Growth in Selected ASEAN Countries - Wardhono, Adhitya; Yaqin, Misbahol; Indrawati , Yulia; Nasir, M. Abd.; Qori'ah, Ciplis Gema (Universitas Negeri Semarang, 2024)
Financial inclusion is an important strategy in economic development. This study aims to measure the level of financial inclusion and examine the effect on economic growth in Selected ASEAN Countries. Empirically, the study uses panel data in the form of annual data during the years 2005-2021. Some of the variables used are financial inclusion, GDP, inflation, and unemployment. The method used in this research is Panel Vector Autoregressive (PVAR). The results of the calculation of the financial inclusion index find that Indonesia's financial inclusion is in the middle category, Malaysia is in the high category, Thailand is in the high category and the Philippines is in a low category. IRF results from PVAR analysis show that financial inclusion has a positive influence on economic growth. This indicates that there is a need for incentives to encourage the growth of financial inclusion so that it is expected to accelerate the pace of economic growth.